2012
DOI: 10.1136/jfprhc-2012-100304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community pharmacy delivered oral contraception service

Abstract: IntroductionIn the UK half of all pregnancies are unplanned and half of teenage pregnancies terminated. Southwark and Lambeth have the highest teenage conception rates in London. In 2009, many teenage pregnancies in Southwark led to terminations. A contraception service was established where qualified pharmacists supplied oral contraception (OC) using a patient group direction (PGD). This service evaluation aimed to assess this service delivered in five community pharmacies.MethodsMonthly data were submitted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 5 publications
5
44
0
Order By: Relevance
“…The mean consultation time was 19 min,12 akin to an SRH clinic appointment time and longer than the average general practice consultation. This may help alleviate HCPs fears that pharmacy consultations would be ‘rushed’, however pharmacists themselves need to be consulted to know whether or not this is feasible within their workload.…”
Section: Discussionmentioning
confidence: 99%
“…The mean consultation time was 19 min,12 akin to an SRH clinic appointment time and longer than the average general practice consultation. This may help alleviate HCPs fears that pharmacy consultations would be ‘rushed’, however pharmacists themselves need to be consulted to know whether or not this is feasible within their workload.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has also identified that pharmacists are not particularly good at providing advice about ongoing contraception, and some women have expressed concerns about receiving advice in the pharmacy about future contraception 9 12 13. A recent study in London, UK concluded that when pharmacists were trained to provide oral contraception by means of an approved PGD they were competent in doing so and women were satisfied with this additional service 14. Simple interventions within the pharmacy that may encourage and help women to start effective contraception after EC have also been the subject of recent research 15.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists have been contracted as partners to provide basic SHS (which Parsons et al 2. showed could provide a satisfactory service).…”
Section: What Does Umbrella Look Like?mentioning
confidence: 99%